(untitled) (Research, Society and Development, 2022)
The use of public spaces and equipment as a place of coexistence enhances personal resources as well as the structure and group operation. Being in collectivity and in the places chosen by adolescents configures a way of living together and a path of professional intervention with a view to promoting mental health. Objective: to map scientific evidence on the use of groups in public places in the health promotion of adolescents. Method: Scope review protocol. We will use as eligibility criteria: data sources via Capes portal: VHL, SCIELO, PUBMED, ERIC, SPELL, CINAHL PEPSIC and PSYCINFO. Productions that report group practices (concept) in public places (context) with adolescents (population) will be included. We will use descriptors and alternative terms DECS/MESH added from Boolean operators to elaborate the search equation. Rayyan and Endnote reference managers will be used. Two reviewers will select the productions from the reading of title and abstract and, will follow up with the full reading of the text for data extraction through excel spreadsheet created for this purpose. Presentation and interpretation of the results: the results included will be classified and categorized thematically, according to Bardin’s content analysis and presented descriptively through the use of tables and tables.